A Novel Bubble-Mixture Method to Improve Dynamic Images in Carbon Dioxide Angiography. (August 2015) - Chang, Te-I; Chan, Chih-Yang; Su, Shing-Kuan; Wang, Shoei-Shen; Wu, I-Hui
Purpose: To present a novel method of preparing carbon dioxide (CO2 ) for contrast enhancement.Technique: CO2 angiography can often produce poor image enhancement, especially in dependent vessels due to buoyancy of the gas. A new technique for premixing the CO2 gas with the patient's blood and dispersing it into the bubble mixture before injection was developed. Comparative dynamic images showed bubble-mixed CO2 angiography had less fragmentation, more even distribution, and more sustainability than the same volume of pure CO2 .Conclusion: The alteration of CO2 gas toward a semiliquid form demonstrates an easy and reproducible concept to improve the dynamic image quality of traditional CO2 angiography.